Artes marciais, formação profissional e escolas de ofício: Análise documental do judô Brasileiro - Drigo, A. J. [UNESP]; Souza Neto, S. [UNESP]; Cesana, J. [UNESP]; Gomes Tojal, J. B A [UNESP] (Desafio Singular, Lda, 2011)
The aim of this research was to describe the process of professional education of judo coaches in Brazil. In order to do this, documental sources were used as means of data collection. Results showed that highly regarded institutions such as Confederação Brasileira de Judô, Federação Paulista de Judô, and Liga Paulista de Judô all support educational structures that resembles the apprenticeship system, that is, education which provide mostly employment-preparation skills for trained labour, in detriment of education on the application of scientific principles aiming at improving sporting performance. In conclusion, Brazilian judo seems to be kept away from the academic formation model and linked to the know how to do traditions. © FTCD/CIDESD.
Martial arts, professional education and the apprenticeship system: Documentary analysis of Brazilian judo
Keywords: Apprenticeship system; Judo; Professional education; Sports coach